DEVELOPMENT OF BEAMA LEARNING MEDIA (FUN LEARNING MATHEMATICS) BASED ON AN ANDROID APPLICATION ON DISTANCE, TIME AND SPEED MATTER IN CLASS V SD - Khairunnisa, Yuniar; Maulana; Isrok’atun (Euclid, 2023)
This article explains the process of developing BEAMA (Fun Learning Mathematics) learning media based on the Android application on distance, speed and time material in class V elementary school, determining the appropriateness of the application through an expert validation process. This research uses the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. The subjects in this research were class V students at SDN Sukamaju Sumedang. The research instruments used were expert validation sheets and teacher and student response questionnaires. The research results are: (1) the development of the BEAMA application is relevant to the needs of the mathematics learning process on distance, time and speed material in class V elementary school, (2) the design of the BEAMA application that has been created is developed into an.apk file, (3) The BEAMA application has the appropriateness of material content in the very appropriate category with a percentage of 92.5%, the appropriateness of the media with a percentage of 94% and the percentage of language experts is 80% in the appropriate category. (4) the BEAMA application received a response from teachers with a percentage of 90%. The BEAMA application has been tested on a limited number of 10 fifth grade elementary school students. In its implementation, students enthusiastically took part in learning using the BEAMA application, student responses to using the BEAMA application obtained a percentage of 88%. The BEAMA application can be used in the classroom learning process to create an effective, interactive and fun learning atmosphere. BEAMA learning media using articulate storyline 3 on speed material has been valid and practical to use.